Long patient conflict essays on women and gender in Australian Christianity - Hutchinson, Mark Peter, 1958-; Campion, Edmund (Sydney, NSW The Centre for the Study of Australian Christianity, Robert Menzies College, Macquarie University, 1994)
Includes bibliographical references.
Keywords: Christianity -- Australia; Christianity -- women; Australia -- civilizaltion